Community-led Watershed-based Water Resources Management: The Case of Balian, Pangil, Laguna - Antonio P. Contreras (Philippine Institute for Development Studies (PIDS), 2004)
In Balian, the presence of indigenous institutions borne by a well entrenched and historically rooted and highly developed sociopolitical arrangement has enabled the local community to effectively link their governance and production activities to the watershed resource, despite opposition from some local political interests. The core of this is the Samahan ng Balian para sa Pagpapauwi ng Tubig, Inc. (SBPTI), a barangay based peoples organization formed in 1926 with the goal of managing the water system sourced from a spring within a small watershed in the Sierra Madre Range. The historical roots of SBPTI have enabled present-day actors, with the assistance of NGO mediators, to deal with conflict and challenges, as they establish order (i.e., govern) in their community vis-à-vis their domestic water needs. While most of the livelihoods in the community are nonresource based, considering that only a small percentage are dependent on the watershed for their immediate livelihoods, it was shown in the Balian case how local mobilization can influence those whose farming activities are within the watershed areas to take on more ecological practices. It also illustrated how people in downstream communities, if properly equipped with the correct ecological perspective on the importance of watersheds in their daily lives, could be directly involved in watershed management. It was obvious from the Balian experience that people can be directly involved in ecological restoration and protection activities in situations where they have full awareness of the opportunity costs should they do otherwise.
Keywords: 330; civil society; community-based watershed resource governance; small watersheds; NGO mediators; Wasserpolitik; Wasserwirtschaft; Philippinen